As construções verbais paratáticas: gramaticalização em italiano - Bomtorin, Patricia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work aims to study, in Italian, the occurrence of a particular type of construction, which are the paratactic verbal constructions (PVCs, henceforth). The constructions focused in this research are formed by two or more verbs inflected, connected or not by the conjunction and, as in: se ne va e piange (go and cry), prendo e me ne vado (I take and go away). Our initial investigation consisted in the documentation of these constructions through corpora from Italian. However, considering that the study of the PVCs are incipient in Italian, its description and analysis still need an exhaustive study, which aims the analysis of its structure and function. Therefore, our objective is to deepen the work begun in scientific initiation level, focusing in the following questions: categorial status of the PVCs as a type of complex predicate not predictable in the ambit of the contemporary Italian grammar (as verbal serialization); and grammaticalization, due to the processes of change involved in the emergence of this construction. Our hypothesis is that the PVCs are considered as focus constructions. We adopt the theoretical presuppositions of the funcional grammar, since this research has as an objective to study the language in use. In the funcionalism, there are some other issues relevant to this work, as: the informational structure, the categorization, the gradience of the complex predicates, the auxiliar constructions, and the verbal serialization. The methodology employed here is constituted by the analysis of the collected data through the corpora CORIS and LABLITA (from the C-ORAL-ROM project), besides a search on the web through Google, and a quantitative research was carried out about these data using the GOLDVARB programme. The analysis made through these corpora focalized in the structure of PVCs; in their function, since we propose their interpretation as focus constructions; in their categorization, due to the fact ...

Esta pesquisa visa a estudar, na língua italiana, a ocorrência de um tipo particular de construção, a saber, as construções verbais paratáticas (CVPs, daqui em diante). As construções focalizadas nesta pesquisa formam-se a partir de dois ou mais verbos flexionados, conectados ou não pela conjunção e, como por exemplo: se ne va e piange (vai-se chora), prendo e me ne vado (pego e vou-me embora). Nossa investigação inicial consistiu na documentação destas construções a partir de corpora do italiano. Todavia, considerando que o estudo das CVPs é incipiente no italiano, sua descrição e análise ainda carecem de um estudo exaustivo, que vise à análise de sua estrutura e função. Desse modo, nosso objetivo é aprofundar o trabalho iniciado em nível de iniciação científica, com foco nas seguintes questões: estatuto categorial das CVPs como um tipo de predicação complexa não previsível no âmbito da gramática do italiano contemporâneo (a saber, serialização verbal); e gramaticalização, tendo em vista os processos de mudança envolvidos na emergência dessa construção. Nossa hipótese é a de que as CVPs sejam consideradas como construções de foco. Adotamos os pressupostos teóricos da gramática funcional, visto que esta pesquisa tem por objetivo estudar a língua em uso. Dentro do funcionalismo, cabe estudar outros pontos caros a este trabalho, como: a estrutura informacional, a categorização, a gradiência da predicação complexa, a auxiliaridade e a serialização verbal. A metodologia empregada aqui consta da análise dos dados coletados a partir dos corpora CORIS e LABLITA (do projeto C-ORAL-ROM), além de buscas na web a partir do site google, sendo que foi efetuada uma pesquisa quantitativa sobre estes dados com uso do programa GOLDVARB. A análise efetuada a partir destes corpora focou na estrutura das CVPs; na sua função, haja vista que propomos sua interpretação como construções...
Keywords: Lingua italiana; Lingua italiana - Gramática; Classificadores (Linguistica); Italian language